Statistical analysis of cyclic performance of fire resistant door set in shopping Centre in Malaysia - Ali, Maisarah (s.n, 2012)
Fire and smoke are major risks to life and property in buildings. As such, fire and smoke have to be controlled and prevented with whatever means and methods that is available in order to keep it out of its destructive and lethal propensity. The concept of keeping the occupants of buildings safe in case of fire relies upon separating whole building into smaller “compartments”. Compartmentalization is a concept in fire protection whereby a building or part of a building, comprising one or more rooms, spaces or stories, constructed to prevent the spread of fire to or from another part of the same building, or adjoining building. This is done by making compartment boundaries which consists of walls, ceilings, and floors to be fire rated. The objectives of the research are to investigate the actual open-closed cyclic performance of fire resistant door set in shopping centers and to compare the actual open-closed cyclic performance of fire resistant door set with the benchmark set by Malaysian Standard. A tabular form was designed to record the actual performance on open-closed cycle of fire resistant door set and it is used a primary tool for data collection. The study conducted at two selected shopping centers in Kuala Lumpur, Malaysia i.e., Sungai Wang Plaza and Low Yat Plaza. The units of the doors were selected based on the building management’s suggestion based on the frequent door usage. The actual counting was carried out by filling the tabular form and a video camera recorder was used as a back-up, especially on the doors in the area with heavy traffic flow. The result shows that out of four door set measured two showed that the actual number of door cyclic movement is higher than stipulated in the Malaysian Standard